Stable transfection of the human parasite Leishmania major delineates a 30-kilobase region sufficient for extrachromosomal replication and expression. - Kapler, G M (1990)
To delineate segments of the genome of the human protozoan parasite Leishmania major necessary for replication and expression, we developed a vector (pR-NEO) which can be reproducibly introduced into L. major. This DNA was derived from a 30-kilobase extrachromosomal amplified DNA bearing the dihydrofolate reductase-thymidylate synthase gene, with the coding region for neomycin phosphotransferase substituted for that of dihydrofolate reductase-thymidylate synthase and a bacterial origin of replication and selectable marker added. G418-resistant lines were obtained at high efficiency by electroporation of pR-NEO (approaching 10(-4) per cell), while constructs bearing an inverted neo gene or lacking Leishmania sequences did not confer resistance. pR-NEO replicated in L. major and gave rise to correctly processed transcripts bearing the trans-spliced miniexon. Molecular karyotype analysis showed that in some lines pR-NEO DNA exists exclusively as an extrachromosomal circle, a finding supported by the rescue of intact pR-NEO after transformation of Escherichia coli. These data genetically localize all elements required in cis for DNA replication, transcription, and trans splicing to the Leishmania DNA contained within pR-NEO DNA and signal the advent of stable transfection methodology for addressing molecular phenomena in trypanosomatid parasites.